2013
DOI: 10.4103/0976-500x.110915
|View full text |Cite
|
Sign up to set email alerts
|

Allopurinol induced granuloma annulare in a patient of lepromatous leprosy

Abstract: Granuloma annulare (GA) is a benign, inflammatory dermatosis involving dermis or subcutis with unknown etiology and poorly understood pathology. GA has characteristic histological features of necrobiosis, granuloma formation and abundant mucin deposition. Various predisposing factors, systemic diseases and drugs have been implicated in the etiology. We hereby describe a case of 70 year old male who was a known case of lepromatous leprosy, taking multidrug therapy for 6 months presented with multiple discrete, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…Infliximab, adalimumab, etanercept [27], dupilumab [28], allopurinol [29], topiramate [30], interferon-alfa [31], amlodipine [32], Other forms of treatment Phototherapy [33], gold therapy [34], injection of collagen [35], mesotherapy [36]…”
Section: Drugsmentioning
confidence: 99%
“…Infliximab, adalimumab, etanercept [27], dupilumab [28], allopurinol [29], topiramate [30], interferon-alfa [31], amlodipine [32], Other forms of treatment Phototherapy [33], gold therapy [34], injection of collagen [35], mesotherapy [36]…”
Section: Drugsmentioning
confidence: 99%
“…4,5 Sun exposure and phototherapy with psoralen combined with ultraviolet A are also reported to precipitate GA. 4,6 Reported drug causes of GA included amlodipine, gold, allopurinol, diclofenac, quinidine, intra-nasal calcitonin and anti-tumour necrosis factor (TNF) agents. 6,7 In one study 15% of patients attributed onset of GA to psychological stress. 5 It has been suggested that GA is due to a delayed type hypersensitivity reaction, 5 but other theories have also been proposed.…”
Section: Aetiologymentioning
confidence: 99%